The composition of bank assets - BOGEN,Jules I (New York : Graduate School of Business Administration, 1961)
How asset changing have affected the commercial banking system,and particularly its ability to serve the future credit needs of a growing economy
obn 23/01/2019
Loans
Keywords: United States; Banks and banking; Liquidity; Bank loans; Bank deposit